PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Elisabet Siahaan; Erni Maria Simatupang (JURNAL AGRICA, 2017)
Human resosurces was of organization success key’s, because of that human resources quality have to develop and control in order to achieve an organization vision. The aim of this research was to analyze the effect off workshop and motivation to labour productivity in PTPN III. The method used a multiple linier regression. The populatin of this research was PTPN III labour that 184 person, while sample of this research took 25% of population as  46 persons. The result show that workshop and motivation positively effect significantly to labour productivity in PTPN III. Partially, workshop effected labour productivity more than motivation. It’s mean that to improve a labour productivity optimally, PTPN III have to give a effective and appropriate workshop to achieve a productive lobour productivity.